Hieracium x stoloniflorum (Asteraceae, Lactuceae), exotic weed new for Argentina - Fernández, Martina; Ezcurra, Cecilia (Instituto de Botánica Darwinion y Museo Botánico de Córdoba, 2009)
Hieracium x stoloniflorum, native from central Europe and northwestern Russia and reported as a putative hybrid between H. aurantiacum and H. pilosella, is first documented for the Argentinian flora. This paper describes this weed and informs about its presence in Río Negro province. Hieracium x stoloniflorum, nativo de Europa central y noroeste de Rusia y reportado como un híbrido putativo entre H. aurantiacum y H. pilosella, se documenta por primera vez para la flora argentina. En este trabajo se describe esta maleza y se informa sobre su presencia en la provincia de Río Negro.